Tauberian theorem for the distributional Stieltjes transformation - D. Nikolić-Despotović; S. Pilipović (International Journal of Mathematics and Mathematical Sciences)
In this paper we use the notion of L-quasiasymptotic at infinity of distributions to obtain a final value Tauberian theorem for the distributional Stieltjes transformation.